Evaluación del aceite de coco (Cocos nucifera) como sustituto de grasas tradicionales en la formulación de chips de malanga (Colocasia esculenta) - Franco Veliz, Yamile Nicolle (2025)
This present study focuses on the evaluation of coconut oil (Coco nucifera) as a substitute for traditional fats in the formulation of taro chips (Colocasia esculenta), analyzing two main types of heat treatments such as frying and baking, controlling their cooking time and temperature to avoid the formulation of unwanted compounds, such as acrolein, ensuring that the chips achieve a balance between texture and flavor. In addition, two types of packaging such as Kraft paper and vacuum packaging were analyzed to determine their influence on the preservation of the organoleptic and microbiological properties of taro chips. Coconut oil extracted by cold pressing was subjected to physicochemical tests such as pH and titratable acidity to determine if it is within the established ranges and suitable for human consumption, while the percentage of ash was determined for the taro chips. Sensory evaluations were conducted with semi-trained panelists to determine the optimal treatment for the malanga chips. Microbiological tests for mold and yeast counts were performed under INEN 1529-10 1998 standards to determine the safety of the product. This study focused on identifying the optimal heat treatment and packaging to create a product that is not only innovative but also high-quality, highlighting coconut oil as a healthy option and offering a safe product